Perilaku Gedung Dengan Perbedaan Kekakuan Antar Lantai - Tommy Iduwin; Dicki Dian Purnama (FORUM MEKANIKA, 2019)
Abstract Earthquake is one of the most frequent disasters in Indonesia. This is due to the location of Indonesia which is located between 3 active plates, namely the Pacific Plate, the Indo-Australian Plate and the Eurasian Plate. While from 2018 to date the biggest and worst earthquake in the Lombok Earthquake that occurred with magnitude reached 7 on the Richter Scale and hammer earthquakes with magnitude 7.4 on the Richter Scale. One of the frequent failures caused by the earthquake is the soft store. Soft story mainly occurs in office buildings, hotels or apartments which generally have a lobby or area that is intentionally made without walls / dividers, either on the ground floor or the upper floors so that inter-floor fuss will be different. In designing and modeling structures, buildings are generally designed with open frame type port without walls. The height of the column can also cause a difference between different floors. This study will compare between the wallless portal model with a higher level at the bottom of the building, the middle of the building and the top of the building, where a high level with smaller stiffness has the potential to be soft (soft story). In this study using ETABS 9.7.2 program with spectrum response dynamic load based on the 2017 earthquake map. Results The structure period of the results of the analysis with the program in the crack cross section condition was obtained at 2.01 seconds. The shape mode for the three PPKBB, PKBT and PKBA building types has met the requirements where in shape 1 and 2 building models are translating towards the x or y axis while in shape 3 mode they are twisted. The required mass participation ratio value is reached at the 90% percentage reached at the 8th shape mode for the PKBB and PKBT buildings. While for PKBA it is reached in the 5th shape mode. Deviation values ​​for the three types of building PKBB, PKBT and PKBA are still within the permit limit. Keywords: earthquake, soft storey, spectrum response